Effectiveness of local community strategies in integrating people with special needs - alguerri, abdrahman; assli, noureddine (sports creativity, 2025)
The issue of care and integration (disabled) people with special needs is one of the most important issues that are all world governments to give top priority in its work, interest in this category take a human dimension, as well as he reflects on the progress of States or its successor, and all international norms and laws let attention to this category, that building a strategy for integrating people with special needs the first step in the right direction. Like other countries, Algeria and with their scientific, economic and cultural interest in this should be the category and the exploitation of resources, financial, material and human resources for the care and the integration of people with special needs whose numbers are increasing year after year.